Dynamic modelling of microalgae cultivation process in high rate algal wastewater pond - Bello, Muhammadu; Ranganathan, Panneerselvam; Brennan, Feargal P. (Elsevier, 2016)
In this work, a comprehensive dynamic mathematical modelling to simulate the production of microalgae in a high rate algal pond (HRAP) is attempted. A synergetic algal–bacterial system comprising various interrelated biological and chemical system processes is presented. The dynamic behaviour of HRAP system is studied by solving mass balance equations of different components which account light intensity and gas–liquid mass transfer. The model predictions are compared with the previously reported studies in the literature. The influence of kinetic and operating parameters, including the supply of CO2, the maximum growth rate, pond depth and dilution rates, on the pond performance are evaluated. The sensitivity analysis of important process parameters is also discussed in this study. The developed model, as a tool, can be used to assess the factors that affect the pond performance criteria, including algal productivity and the dynamics of nutrient requirements.
Keywords: HRAP; Microalgae; Mathematical modelling; Wastewater treatment